The Impact of Air Pollution on Healthcare Expenditure for Respiratory Diseases: Evidence from the People’s Republic of China - Li L; Du T; Zhang C (Dove Medical Press, 2020)
Lele Li,1,* Tiantian Du,2,* Chi Zhang3 1School of Public Policy and Management, Tsinghua University, Beijing 100084, People’s Republic of China; 2Institute for Hospital Management, Tsinghua University, Shenzhen 518055, People’s Republic of China; 3Chinese Academy of Fiscal Sciences, Beijing 100142, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lele LiSchool of Public Policy and Management, Tsinghua University, No.1 Tsinghua Yard, Haidian District, Beijing 10084, People’s Republic of ChinaTel +86-010-6147-2626Email lilele1211@163.comBackground: Air pollution is an important factor in health outcomes and health-care expenditure. It has become an important issue of global concern. The objective of this study was to explore the influence of air pollution on the economic burden of respiratory diseases using different levels of PM2.5.Methods: Starting from the demand side, we took the 3,546 patients in the Respiratory and Critical Care Department of a tertiary hospital in Beijing between 2013 and 2015 as examples, combining daily air-quality data using a generalized linear regression–analysis model to explore the impact of air pollution on health-care expenditure on a microindividual level.Results: We found that PM2.5 had a significant impact on health-care expenditure on respiratory diseases. It had a positive impact on total health-care expenditure, drug expenditure, and antibiotic expenditure. The impact of different levels of air pollution on the health care–expenditure burden of disease was heterogeneous. As the air-pollution index increased, health care–expenditure burden of respiratory diseases also gradually raised. The impact of PM10 and air-quality index had a positive impact on health-care expenditure for respiratory diseases. Air pollution had a significant impact on health care–expenditure burden of respiratory diseases. The effect of length of stay on various health-care expenditure was significantly positive.Conclusion: The impact of mortality-risk classification on various health-care expenditure is significant. Therefore, policy-making must take into account both the supply side and the demand side of health-care services. Furthermore, the government should strengthen environmental governance, pay attention to the heterogeneity of the health care–expenditure burden affected by environmental pollution, improve the medical insurance system, and improve the health of residents to reduce the health care–expenditure burden.Keywords: air pollution, PM2.5, respiratory diseases, health care–expenditure burden, individual health level